Policies adopted to tackle the pandemic in Italian schools: institutional interventions - Palmeri, Ezia (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The global spread of the coronavirus (Covid-19) has led to unprecedented disruptions in schools worldwide in 2020. In Italy, from 5 March 2020, in-presence teaching activities in nursery schools and schools of all levels were suspended throughout the country. At the same time, distance learning has been activated, with particular attention to the specific needs of students with disabilities. The article aims to highlight the role assumed by the institutional interventions carried out in the emergency situation, aimed at reconciling the safeguarding of the right to study and the protection of the health of students and school staff.